EAT AND/OR BE EATEN: THE EVOLUTIONARY ROOTS OF VIOLENCE? - Conradie, Ernst M. (Scriptura, 2015)
This contribution raises the question about where things have gone wrong in evolutionary history. In classic Christian discourse it is typically assumed that the primary problem is human sin, while the problem of natural evil is emphasised elsewhere. It seeks to test the distinction between natural suffering and socially-induced forms of suffering by exploring the roots of violence between species with reference to the emergence of the act of eating in evolutionary history. It draws on a corpus of recent literature on the consumption of food, with specific reference to the work of Edward Farley, Sallie McFague and Norman Wirzba, in order to address the following question: Is the violence associated with what Christians would redescribe as sin merely an extrapolation of the ‘violence’ embedded in the act of eating? The conclusion from this survey seems to be that an Augustinian approach is indeed less plausible and more counter-intuitive than Manichean or Pelagian assessments of where things have gone wrong in evolutionary history. If so, this would have far-reaching consequences for moral formation. The conclusion is offered here in the hope that it would be refuted by others!